A Relative Study of Data Mining and Big Data on IoT ’s Data Streams - Mohmmad, Sallauddin; Nawaz Pasha, Syed; Ramesh, Dadi; Shabana (International Journal of Computer Sciences and Engineering, 2025)
the huge amount of data produced and captured by the Internet of Things (IoT) in current situations. IoT data created by several applications such as from smart cities, monitoring system, health care, object detecting systems and smart systems etc. which all produce the continues data streams. But data of IoT recognized with RFID signal their size is near to 20 bytes. So that it is requiring of special procedures for analyzing, managing and mining the IoT stream data which is identified by RFID. Several software tools have been developed for mining the stream data relatively Big Data tools. While most current research looking into data mining and relative big data tools which are on machine learning of distributed and non-distributed systems with respect to IoT stream data. This paper focused on IoT data format, different kind stream data mining tools according to mining steps and few Big Data tools relative with data mining for handling the stream data of IoT.